Ărramăt: an example of Indigenous Peoples’ holistic approach of health and well-being - Mariam Wallet Aboukakrine; Brenda Parlee; Zoé Boirin-Fargues; Alejandro Argumedo; Clint Carroll; Maria Eugenia Choque Quispe; Hanna Guttorm; Carwyn Jones; Irja Seurujärvi-Kari; Wasiq Silan/I-An GAO (高怡安); Prasert Trakansuphakon; Sherry Pictou (FACETS)
Status quo frameworks are highly Eurocentric and narrow in scope protecting; biodiversity conservation in many parts of the world and reflect a kind of dichotomized conservation that has created and perpetuated patterns of poverty, food insecurity, and socio-economic marginalization, particularly among Indigenous Peoples. By dichotomized conservation, we mean an approach to conservation that is not taking into consideration the intrinsic interdependence of environment, people, and all the species. It is the management of conservation of different ecosystems and species separately. This framework is opposed to the Indigenous approach to conservation in which people cannot think about their health and well-being without thinking about the health and well-being of Mother Earth. New conceptualizations of biodiversity are needed that are holistic in nature and confront these historical and systemic patterns of exclusion of Indigenous Peoples.